Acid-base disturbances in critically ill patients - Meza García, Mónica (2011)
The current understanding of acid-base physiology states that all changes in the blood, pH, as well as variations in a healthy state and during disease occur through changes in 3 variables: (a) Carbon dioxide (CO2), (b) electrolyte relative concentration, and (c) weak acid concentration. Internal milieu and acid-base disturbances generate alterations inthree areas: a) direct damage in multiple organs and systems, (b) a compensatory response to the disturbance, which may be suitable or incomplete, and (c) functional alterations in immune cells. The classically used Henderson-Hasselbalch equation for the classification of acid-base disorders in respiratory (abnormal CO2) and metabolic (abnormalbicarbonate) and for the “anion gap” calculation, but this equilibrium  equation assumes that albumin and phosphate concentrations are very close to normal, a condition that is not necessarily certain in most critically ill patients, so the anion gap must be corrected. The Stewart’s model proposes that pH varies according to 3 independent variables: thestrong ion difference (DIF), non-volatile weak acids (Atot), and pCO2. Consequently, the merit of this approach is to merge acid-base status and electrolyte changes in a single interpretation. Therapy of acid-base disturbances in critically ill patients is focused on early detection of such conditions, using a comprehensive approach involving both theclassical theory and Stewart’s theory so that adequate management of the underlying condition may be achieved.